Policy Briefing on Child Protection Policy of Ethiopia in Emergencies (Global Journal of Human-Social Science, 2018)
Children are the future generation who will be socialized and grown in a good healthy condition because they are the future adults and development in overall the world If the children have not necessarily been socialized they shall be exposing different faces for their physical mental psychological moral and community development at large 48 6 of Ethiopia people are children who are below 15 years old Among 48 6 nearly 18 are under the age of 5 years which means 37 of the entire below 15 years old and these have encountered to the challenges of child trafficking child labor sexual abuse orphan and vulnerable and other related problems Despite the fact that the Ethiopia government has launched lot policies such as child protection policy for tackling such problems these have still been occurring and expanding in different districts in a country without the discrimination of ethnicity language and nations and nationalities More specifically in fact getting available data on human trafficking in general and child trafficking in particular is difficult owing to its illegal hidden the extent and magnitude of trafficking activities and problems more than 869 567 children who the age between 10 to 14 were illegally migrating from Ethiopia On other issue 70 in Ethiopian girls are sexually abused and harassed and 30 girls were raped at least one time in their life before reaching the age of eighteen However nearly five out of ten girls assured that they were averagely raped three to ten time in their life span On child labor problem from 48 6 of children who below 15 years old in Ethiopia half of the children were active economically in the age group 10-14 in the country among seven million children in the listed age group Out of the entire children population in Ethiopia who faced to the challenges of child labor nearly six out of ten children and one out of ten children lived in rural and urban respectively These empirical evidenc
Keywords: child; protection; policy; briefing; ethiopia